Stone maidens [large type] - Richards, Lloyd Devereux (Center Point Large Print, 2023)
"As the chief forensic anthropologist for the FBI's Chicago field office, Christine Prusik has worked her fair share of bizarre cases. Yet this one trumps them all: a serial killer is strangling young women and dumping their bodies in the steep, forested ravines of southern Indiana. With each victim, the killer leaves a calling card: a stone figurine carved like the spirit stones found among the native tribes of Papua New Guinea -- the same tribes Prusik worked with a decade earlier while doing field research. The personal nature of the similarity is eerie and, frankly, terrifying; Prusik still carries trauma from her time in the field. As the dark details continue to surface, Prusik has to wonder if the connection is real or if her nightmares have finally wormed their way into her waking life."--